Motivation and rewarding in knowledge-intensive organizations - A case study - Korpelainen, Kirsi (My University, 2016)
This study examines the motivation of specialists and rewarding at the media agency Case A. The purpose of the study is to find out what motivates specialists at Case A and which reward methods they prefer. Knowledge-intensive organizations are used as a context, as Case A can be categorized into a knowledge-intensive organization. The theoretical part covers different motivation theories of which content and process theories are explained in more detail. The motivation theories explain how people are motivated in general. Moreover, theory of rewarding is covered with a focus on employee rewarding. The purpose of rewarding is to reward employees fairly in order to guide employees towards an organization’s values and strategic goals. Reward methods are diversified into tangible and intangible methods and examples are presented in order to comprise an adequate understanding of the tools organizations have in their use. However, the focus of this study is on knowledge workers and therefore the special features related to their motivation and reward preferences are covered. The contribution of knowledge workers is vital to the competitive success of an organization and consequently their motivation to perform excellently is important for the organizations. Interesting work is generally the most important motivator, and a specialist desires to move forward, succeed and learn. Moreover, operational autonomy and task achievement are important. The data for the empirical part was acquired from eleven semi-structured interviews. According to the interviews, the most important motivators for employees are meaningful and challenging work, development possibilities, and appreciation and recognition of work. Moreover, monetary rewards such as bonuses are perceived to be motivating for some employees.
Keywords: motivation; rewarding; knowledge-intensive organizations; specialists; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|